Investigation of coenzyme Q10 status, serum amyloid-β, and tau protein in patients with dementia - Chang, Po-Sheng; Chou, Hsi-Hsien; Lai, Te-Jen; Yen, Chi-Hua; Pan, Ji-Cyun; Lin, Ping-Ting (Frontiers in Aging Neuroscience, 2022)
Objectives: Dementia is an oxidative stress-related disease. Coenzyme Q10 is a nutrient that occurs naturally in the human body and acts as an antioxidant. The purpose of this study was to investigate the relationships of coenzyme Q10 status, biomarkers for dementia (amyloid β and tau protein), and antioxidant capacity in patients with dementia. Methods: Eighty dementia patients aged ≥ 60 years and with a Mini Mental State Examination (MMSE) score ≤ 26 were enrolled. The levels of coenzyme Q10, total antioxidant capacity (TAC), amyloid β, and tau protein were measured. Results: A total of 73% of patients had a low coenzyme Q10 status. Patients with low coenzyme Q10 status had a significantly higher level of serum amyloid β-42 and amyloid β-42/40 ratio (p < 0.05). Coenzyme Q10 status was significantly correlated with the values of TAC, MMSE score, amyloid β-42, and amyloid β-42/40 ratio (p < 0.05) but not with tau protein. Additionally, a high proportion of moderate dementia patients were found to have low coenzyme Q10 status (p = 0.07). Conclusion: Patients with dementia suffered from coenzyme Q10 deficiency, and the degree of deficiency was related to the level of amyloid-β and antioxidant capacity. Since adequate level of coenzyme Q10 may delay the progression of dementia, monitoring coenzyme Q10 status in patients with dementia is necessary.